The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1149/1.3111904
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of Nonflammable Organo-Fluorine Compounds for Lithium Ion Batteries

Abstract: The electrochemical behavior of organo-fluorine compounds with antioxidation ability has been investigated. Oxidation currents of fluorine-compound-containing ethylene carbonate (EC)/diethyl carbonate (DEC) solutions were much smaller than those of EC/DEC and EC/DEC/propylene carbonate (PC) at potentials higher than 6 V vs Li/Li+ . Electrochemical reduction of fluorine compounds started at ca. 2 V vs Li/Li+ , higher than those for EC, DEC, and PC. However the first coulombic efficiencies for natural graphite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
78
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 27 publications
5
78
0
1
Order By: Relevance
“…In addition, when Tafel polarization measurements were performed, the novel electrolytes resulted in the least amount of electrode polarization and the highest limiting current densities implying facile lithium intercalation/de-intercalation kinetics. Similar results were reported on bis(2,2,3,3-tetrafl uoropropyl) carbonate and bis(2,2,3,3,3-pentafl uoropropyl) carbonate in Scheme 2.9 [ 31 ]. …”
Section: Fluorinated Linear Carbonatessupporting
confidence: 87%
“…In addition, when Tafel polarization measurements were performed, the novel electrolytes resulted in the least amount of electrode polarization and the highest limiting current densities implying facile lithium intercalation/de-intercalation kinetics. Similar results were reported on bis(2,2,3,3-tetrafl uoropropyl) carbonate and bis(2,2,3,3,3-pentafl uoropropyl) carbonate in Scheme 2.9 [ 31 ]. …”
Section: Fluorinated Linear Carbonatessupporting
confidence: 87%
“…2. These molecules have traditionally been used in specialized applications such as coolants and supercapacitors, and their use in Li-ion batteries is relatively new [5,6,74,78]. Regardless, these molecules have shown increased stability toward oxidation, better thermal stability, and low flammability.…”
Section: Fluorinated Carbonatesmentioning
confidence: 99%
“…Thus, fluorinated carbonates, especially linear carbonates, are excellent candidates for the low-temperature Li-ion batteries for space and deep-sea missions. Last but not least, the low-flammability to non-flammability of fluorinated compounds could potentially improve the safety of Li-ion batteries [5,6].…”
Section: Fluorinated Carbonatesmentioning
confidence: 99%
“…Fluorinated organics may be good candidates for electrolyte solvents. Fluorinated cyclic and linear carbonate compounds possess desirable physical properties as lithium-ion battery electrolyte, which are imparted by the presence of the fluorine substituents, such as low melting point, increased oxidation stability, and less flammability [48,49]. In fact, fluorinated cyclic carbonate has been reported as a cosolvent by McMillan [50] and Nanbu [51], and as an SEI formation additive for graphite [52] and silicon [53] anodes.…”
Section: High Voltage Electrolytesmentioning
confidence: 99%
“…A series of fluorinated linear carbonates was designed and synthesized by Smart et al [54] at NASA's Jet Propulsion Laboratory as new electrolyte components to improve the low temperature performance of the lithium-ion battery for deep space applications. Achiha et al [49,55] and Arai [56] separately reported the fluorinated carbonates and fluorinated ethers as nonflammable electrolytes or as new solvents for nonaqueous lithium-ion battery electrolytes.…”
Section: High Voltage Electrolytesmentioning
confidence: 99%